Associação entre medidas clínicas, funcionais e fator neurotrófico derivado do cérebro (BDNF) em indivíduos após acidente vascular encefálico (AVE) na fase aguda - Marcela Aline Fernandes Braga (2016)
The brain-derived neurotrophic factor (BDNF) play a significant role in different aspects of the development and functioning of the nervous system, including neurogenesis, differentiation, neuronal survival and synaptic plasticity. The biochemical, physiological and functional changes resulting from ischemia can be influenced by BDNF levels. However, information this neurotrophin levels and its association with clinical and functional measures inpatients in the acute stroke are still inconclusive. In this study, patients with ischemic stroke admitted to a stroke unit of Belo Horizonte were submitted to serial venous blood samples were taken in three times (in 24 hours after ischemia, 72 hours and in the hospital discharge) to measure plasma levels of BDNF by ELISA technique and evaluations of functional status were investigate about structures and body functions and functional level according to the International Classification of functioning, Disability and Health. This prospective study involved Fifty individuals, the mean age was 65.1 (±11.8) years. When comparing the clinical measures and functional at the time of admission and discharge, statistical difference was found for the severity of stroke (Scale of the National Institutes of Health of the United States of America, p <0.001), cognitive function (Mini Mental State Examination, p = 0.0014), Assessment of Motor Recovery after Stroke (Fulg Meyer, p <0.001) and functional level (modified Rankin Scale, p = 0.003 and functional Independence Measure, p <0.001). The grip strength of the affected side was smaller than the unaffected side in two moments (p=0.003 and p =0.007, respectively), but there was no improvement of the affected limb strength (p=0.242). Mean concentration of BDNF was 10148,6 (7522,1 13142,3) pg/ml in admission; 8499,2 (7108,6 11916,7) pg/ml after 72 hours and 9312,8 (6800,4 12006,1) discharge, in median (1st and 3rd percentiles), with no statistically significant difference (p=0.915). Correlations were found between BDNF levels and the functional level assessed by the Functional Independence Measure (motor score: rs =0.290, p=0.041; total score: rs =0.285, p=0.045). The change in BDNF levels may have occurred only at the central level, with no impact on changes in peripheral levels, while BDNF is able to cross the blood brain barrier. The severity of stroke, cognitive function, as well as strength and upper limb function on the affected side were not affected by BDNF levels in the sample. However, higher levels of BDNF resulted in higher level of functional independence, and less need for assistance to perform functional activities in the acute phase. The main limitation of this study is the factor we did not control the time of day that the collection of blood sample due to the specific demands inherent in the admission process was carried out. Still, corroborates literature data also show that BDNF levels were not modified in the first days after stroke and shows the association between these levels and the functional outcome in the acute phase.